Coffee Grounds and Coconut Husk in Layered Filter Treatment for Efficiency Removal and Degradation Capacity of Pollution Parameters in North Aceh Waters - Cut Meurah Nurul 'Akla; Arina Ruzanna; Anis Nugrahawati; Rahma Fitria; Rian Firdaus; Imanullah Imanullah; Aldo Dermawan; Afif Tri Putra; Andi Saputra Simanjuntak; Ichsan Kamil Mandhay (Institut Teknologi Sepuluh Nopember, 2023)
Polluted estuaries can result in oxygen depletion, accumulation of toxic substances and heavy metals, and become a source of pathogens that are threaten for cultivated aquatic biota and coastal tourists. This research aims to analyze 1) pollution index; 2) status of water pollution in Bangka Jaya and Tanoh Anoe Regencies; and 3) testing the level of effectiveness of Layered Filtered Treatment (LFT) using analysis of removal efficiency and degradation capacity on water quality. LTF is a filtration media that composed of coconut husk, membrane and coffee grounds made into briquettes, LFT used to filter polluted estuary waters. The pollution parameters analyzed at Bangka Jaya were nitrate, phosphate, Escherichia coli bacteria and ammonia, while the pollution parameters at Tanoh Anoe were heavy metals Pb and Cd. The research results showed that the pollution status of Bangka Jaya estuary (A1) and Bangka Jaya coastal waters (A2) are moderately polluted, with indices at stations A1, A2 and A3 respectively is 9.19; 8.42; and 8.42. Meanwhile, the water pollution status in Tanoh Anoe estuary are heavily polluted (station B1) and moderately polluted (station B2) with the pollution index at each station being 14.07 and 9.36. The conclusion of this research is that LFT has not been proven capable of removing and degrading the pollutant parameters nitrate, phosphate, E.coli bacteria and ammonia, however the LFT method has been proven capable of increasing dissolved oxygen, stabilizing sea acid, temperature and also water salinity. LFT has also been proven to be able to prevent ocean acidification with a degradation capacity percentage of 6.60%.